Hard carbon composite material, preparation method thereof, negative plate and battery
By using the condensation reaction of sulfonated dioxazole polymer with resin and the staged carbonization process in the resin-based hard carbon material, a hard carbon composite material with a cladding layer is formed, which solves the problems of insufficient reversible specific capacity, first effect and cycle stability of the existing resin-based hard carbon materials in the negative electrode field of sodium ion battery, and achieves high sodium storage capacity and excellent magnification and cycle stability.
Patent Information
- Application Number
- CN202510220426.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-06-27
AI Technical Summary
The existing resin-based hard carbon materials have insufficient reversible specific capacity, first effect and cycle stability in the negative electrode field of sodium ion battery, which limits its development.
The sulfonated diozole polymer and the resin are used to condensate in a solvent to form a hard carbon composite material precursor, and the hard carbon composite material is obtained through a segmented carbonization process to obtain a resin-based hard carbon and a surface of the organic coating formed by chemical cross-linking of the sulfonated diozole polymer and the resin.
The reversible specific capacity, first effect and cycle stability of resin-based hard carbon materials are improved, rate magnification performance is enhanced, and Na consumption is reduced through the passivation of the coating layer, and conductivity and pore structure stability are improved.
Smart Images

Figure CN120221609A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and specifically, to a hard carbon composite material, a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] Most of the hard carbon negative electrode materials are prepared by pyrolysis of biomass carbon precursors. Since the biomass preparation route of hard carbon has both high performance and low cost advantages, and the outstanding feature of biomass raw materials is wide source, green and environmental protection, and most of them are by-products or wastes in the agricultural production process. However, the preparation of biomass hard carbon is restricted by differences in regions, seasons, etc., which in turn leads to unstable performance of the prepared hard carbon materials. In terms of performance, biomass-based hard carbon has defects such as low initial efficiency and low tap density, resulting in low energy density during the battery design process.
[0003] Currently, polymer resin materials are also often used to prepare hard carbon negative electrodes. The resin precursor structure is simpler than natural biomass polymers and has a controllable molecular weight. In addition, relevant molecular structures can be selected or designed to achieve the purpose of constructing closed pore structures and carbon defect active sites, with good operability. However, the existing resin-based hard carbon materials are restricted in their further development in the field of negative electrodes for sodium ion batteries due to their poor reversible specific capacity and cycling performance. Summary of the Invention
[0004] In view of this, the present invention is committed to providing a hard carbon composite material, a preparation method thereof, a negative electrode sheet and a battery, which are beneficial to improving the reversible specific capacity, initial efficiency, cycling stability and rate performance of resin-based hard carbon materials in batteries.
[0005] In order to solve the above technical problems, the present application is implemented as follows:
[0006] According to the first aspect of the present application, the present invention provides a preparation method of a hard carbon composite material, comprising the following steps:
[0007] Mix a resin, a sulfonated oxadiazole polymer and a solvent to obtain a mixed solution, and carry out a condensation reaction to obtain a hard carbon composite material precursor;
[0008] Carry out carbonization on the hard carbon composite material precursor to obtain a hard carbon composite material.
[0009] In any embodiment, the sulfonated oxadiazole polymer includes sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole).
[0010] In any embodiment, the preparation method of the sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole) comprises the following steps:
[0011] Hydrazine sulfate, phthalic acid, and 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole are mixed and heated to obtain sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole).
[0012] In any embodiment, the mass ratio of the hydrazine sulfate, phthalic acid, and 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole is 1:(2 - 3):(4 - 6).
[0013] In any embodiment, the heating temperature range is 80 - 120 °C.
[0014] In any embodiment, the resin includes a resin containing a hydroxyl functional group.
[0015] In any embodiment, the resin includes at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, melamine-formaldehyde resin, polyester resin, vinyl resin, or polyether resin; preferably, the phenolic resin includes thermoplastic phenolic resin.
[0016] In any embodiment, the resin includes spherical resin.
[0017] In any embodiment, the solvent includes an aqueous alcohol solution.
[0018] In any embodiment, the aqueous alcohol solution includes at least one of aqueous ethanol solution, aqueous n-propanol solution, or aqueous propylene glycol solution.
[0019] In any embodiment, the volume ratio of alcohol to water in the aqueous alcohol solution is 1:(2 - 8).
[0020] In any embodiment, the concentration of the resin in the mixed solution is 0.1 - 1 g / mL.
[0021] In any embodiment, the mass ratio of the sulfonated oxadiazole polymer to the resin is 1:(5 - 20).
[0022] In any embodiment, the temperature of the condensation reaction is 150 - 200 °C, the time of the condensation reaction is 5 - 15 h, and the pressure of the condensation reaction is 0 - 3 MPa.
[0023] In any embodiment, after the condensation reaction, the obtained product is sequentially filtered, washed, and dried to obtain a precursor of the hard carbon composite material.
[0024] In any embodiment, the carbonization includes staged carbonization, and the staged carbonization includes two-stage carbonization to four-stage carbonization.
[0025] In any embodiment, the heating rate of the first-stage carbonization in the segmented carbonization is 1 to 2 °C / min, the final temperature of the first-stage carbonization is 90 to 110 °C, and the holding time at the final temperature of the first-stage carbonization is 1 to 3 h.
[0026] In any embodiment, the heating rate of the second-stage carbonization in the segmented carbonization is 4 to 6 °C / min, the final temperature of the second-stage carbonization is 200 to 300 °C, and the holding time at the final temperature of the second-stage carbonization is 2 to 3 h.
[0027] In any embodiment, the heating rate of the third-stage carbonization in the segmented carbonization is 2 to 3 °C / min, the final temperature of the third-stage carbonization is 500 to 700 °C, and the holding time at the final temperature of the third-stage carbonization is 4 to 7 h.
[0028] In any embodiment, the heating rate of the fourth-stage carbonization in the segmented carbonization is 2 to 3 °C / min, the final temperature of the fourth-stage carbonization is 1000 to 1400 °C, and the holding time at the final temperature of the fourth-stage carbonization is 2 to 3 h.
[0029] In any embodiment, the atmosphere for carbonization includes at least one of nitrogen, argon or helium.
[0030] In any embodiment, the flow rate of the atmosphere for carbonization is 50 to 100 mL / min.
[0031] In any embodiment, after the carbonization, it further includes: cooling the obtained product after carbonization to 20 to 30 °C.
[0032] According to the second aspect of the present application, the present invention provides a hard carbon composite material, which is prepared by the preparation method of the hard carbon composite material as described above.
[0033] According to the third aspect of the present application, the present invention provides a negative electrode sheet, which includes the hard carbon composite material prepared by the above method or the above hard carbon composite material.
[0034] According to the fourth aspect of the present application, the present invention provides a battery, which includes the hard carbon composite material prepared by the above method, or the above hard carbon composite material, or the above negative electrode sheet.
[0035] Through the above technical solutions, the beneficial technical effects of the present invention are:
[0036] In the embodiments of the present application, for the provided hard carbon composite material and its preparation method, a sulfonated oxazole polymer is selected as the coating agent to undergo a condensation reaction with the resin in a solvent, so that the organic matter is uniformly connected to the surface of the resin, and then carbonized to obtain a resin-based hard carbon as the core and a derivative carbon of the organic matter coating layer formed by chemical cross-linking of the sulfonated oxazole polymer and the resin on the surface. The sulfonic acid groups in the sulfonated oxazole polymer undergo a condensation reaction with the hydroxyl groups on the resin surface to generate sulfonate groups, thereby enabling the sulfonated oxazole polymer to be uniformly coated on the resin surface, achieving precise and uniform "face-to-face" coating. The coating layer has a passivation effect, which can reduce the Na consumption caused by the formation of SEI, improve the first-cycle Coulombic efficiency. The N groups contained in the sulfonated oxazole polymer realize N doping while coating the resin, improve the conductivity, expand the layer spacing, increase the pore structure and enhance the stability; moreover, the sulfonated oxazole polymer has flexibility, which can to a certain extent improve the flexibility problem existing in the preparation of the resin-based hard carbon material for the electrode. Therefore, the hard carbon composite material exhibits high sodium storage capacity, excellent rate performance and cycle stability in terms of electrochemical performance. In addition, when ethanol is selected as the solvent during the condensation reaction, a large number of micropores can be formed on the material surface to form a three-dimensional hierarchical pore structure. After subsequent calcination treatment, the micropore structure changes from open pores to closed pores, which is beneficial to the storage of sodium ions.
[0037] Other features and advantages of the present invention will be described in detail in the subsequent specific embodiments section. Brief Description of the Drawings
[0038] The drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation to the present invention.
[0039] Figure 1 Shown is the scanning electron microscope image of the hard carbon composite material prepared in Example 1;
[0040] Figure 2 Shown is the transmission electron microscope image of the hard carbon composite material prepared in Example 1;
[0041] Figure 3 Shown are the N2 adsorption / desorption curves of the hard carbon composite materials prepared in Example 1 and Comparative Example 1. Specific Embodiments
[0042] The present invention discloses a hard carbon composite material, a preparation method thereof, a negative electrode sheet and a battery. Those skilled in the art can draw on the content of this article and appropriately modify the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all regarded as included in the present invention. The methods and applications of the present invention have been described through preferred embodiments. It is obvious that relevant personnel can make changes or appropriate alterations and combinations to the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0043] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0044] In the ranges disclosed herein, the endpoints and any values are not limited to the exact ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range or individual point values, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.
[0045] If there is no special instruction, all implementation manners and optional implementation manners of the present application can be combined with each other to form a new technical solution.
[0046] If there is no special instruction, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0047] If there is no special instruction, the "including" and "comprising" mentioned in the present application mean open-ended, and can also be closed-ended. For example, the "including" and "comprising" can mean that other components not listed can also be included or comprised, or only the listed components can be included or comprised.
[0048] The electrochemical device includes a positive electrode plate, a negative electrode plate and a separator; the negative electrode plate includes a negative active material, and the negative active material includes graphite, hard carbon, etc. In recent years, it has almost reached the theoretical capacity limit of graphite, and there is little room for further improvement. Due to the advantages of small volume expansion, strong fast charge and discharge ability, and high specific capacity per gram of hard carbon materials, extensive research has been carried out. At present, hard carbon materials mainly include bio-based hard carbon materials and resin-based hard carbon materials. The resin-based hard carbon material precursor has the advantages of simple polymer and controllable molecular weight compared with the bio-based hard carbon material precursor. At the same time, the relevant molecular structure can be selected or designed, and the operability is strong. However, the reversible capacity of resin-based hard carbon materials is low and the cycle performance is poor, which limits their further development in electrochemical devices.
[0049] In view of this, the present invention provides a hard carbon composite material, a preparation method thereof, a negative electrode sheet and a battery, which can improve the reversible specific capacity, first efficiency, cycle stability and rate performance of hard carbon materials in the battery. The following will explain the present application and optional implementation manners in more detail.
[0050] [Preparation method of hard carbon composite material]
[0051] In some embodiments, a preparation method of a hard carbon composite material is provided, including the following steps:
[0052] Mix a resin, a sulfonated dioxazole polymer and a solvent to obtain a mixed solution, and carry out a condensation reaction to obtain a hard carbon composite material precursor;
[0053] Carburize the hard carbon composite material precursor to obtain a hard carbon composite material.
[0054] In the present application, a sulfonated dioxazole polymer is selected as the coating agent, which undergoes a condensation reaction with the resin in the solvent, so that the organic coating uniformly coats the surface of the resin; while the sulfonated dioxazole polymer coats the resin, nitrogen (N) doping is achieved, the layer spacing is expanded, the pore structure is increased and the stability is improved. Therefore, the electrochemical performance shows high sodium storage capacity, excellent rate and cycle stability; then carburization is carried out to obtain a resin-based hard carbon core and an organic coating-derived carbon formed by chemical cross-linking of the sulfonated dioxazole polymer and the resin on the surface.
[0055] Specifically, the sulfonic acid groups in the sulfonated oxadiazole polymers react with the hydroxyl groups on the resin surface to form sulfonate groups, thereby enabling the sulfonated oxadiazole polymers to uniformly coat the resin surface, achieving precise and uniform "face-to-face" coating. The coating layer has a passivating effect, which can reduce the Na consumption caused by the formation of SEI, improve the first-cycle Coulombic efficiency. The sulfonated oxadiazole polymers contain N groups, which can achieve N doping while coating the resin, improve the conductivity, expand the layer spacing, increase the pore structure and enhance the stability. Moreover, the sulfonated oxadiazole polymers are flexible, which can, to a certain extent, improve the flexibility problem of resin-based hard carbon materials during the preparation of electrodes. Therefore, the electrochemical performance of the hard carbon composite materials shows high sodium storage capacity, excellent rate performance and cycle stability.
[0056] Therefore, the hard carbon composite material proposed in this application selects sulfonated oxadiazole polymers as the coating agent, which undergoes a condensation reaction with the resin in a solvent, enabling the uniform connection of organic substances on the resin surface, and then carbonization to obtain a resin-based hard carbon core and an organic matter coating layer-derived carbon formed by chemical cross-linking of sulfonated oxadiazole polymers and the resin on the surface. The sulfonated oxadiazole polymers can uniformly coat the resin surface, have a passivating effect, can reduce the Na consumption caused by the formation of SEI, and improve the first-cycle Coulombic efficiency. At the same time, nitrogen (N) doping is achieved, the layer spacing is expanded, the pore structure is increased and the stability is enhanced, and the electrochemical performance shows high sodium storage capacity, excellent rate performance and cycle stability.
[0057] In this application, the term "resin" generally refers to an organic polymer that has a softening or melting temperature range when heated, has a tendency to flow under the action of external force when softened, and is solid, semi-solid or sometimes liquid at room temperature.
[0058] In this application, the term "oxadiazole polymer" refers to a polymer compound containing an oxadiazole ring structural unit, and the oxadiazole ring structure mainly includes 1,3,2-oxadiazole ring or 1,3,4-oxadiazole ring.
[0059] In this application, the term "sulfonation" refers to the introduction of a sulfonic acid group (-SO3H) into an organic compound molecule.
[0060] By introducing sulfonic acid groups into oxadiazole polymers, sulfonated oxadiazole polymers are obtained. The sulfonic acid groups react with the hydroxyl groups on the resin surface to form sulfonate groups, thereby enabling the sulfonated oxadiazole polymers to uniformly coat the resin surface, achieving precise and uniform "face-to-face" coating.
[0061] In some specific embodiments, the sulfonated oxadiazole polymer includes, but is not limited to, sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole).
[0062] In some specific embodiments, the preparation method of sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole) comprises the following steps:
[0063] Mix hydrazine sulfate, phthalic acid and 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole, and obtain sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole) by heating.
[0064] In some specific embodiments, the mass ratio of hydrazine sulfate, phthalic acid and 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole is 1:(2 - 3):(4 - 6). As an example, the mass ratio of hydrazine sulfate, phthalic acid and 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole can be any one of the point values of 1:2:4, 1:3:4, 1:2:5, 1:3:5, 1:2:6 or 1:3:6 or the range values between any two of them. Hydrazine sulfate and phthalic acid are used as dehydrating sulfonating agents. By controlling the mass ratio of hydrazine sulfate, phthalic acid and 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole within the above range, sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole) with excellent performance can be prepared.
[0065] In some specific embodiments, the heating temperature range is 80 - 120°C. As an example, the heating temperature range can be any one of the point values of 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C or the range values between any two of them.
[0066] Optionally, the heating method can be an oil bath, but is not limited thereto. For example, an electric heating method can also be used, etc.
[0067] As an example, the preparation of sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole) specifically comprises the following steps:
[0068] Mix 1 g of hydrazine sulfate, 2 - 3 g of phthalic acid and 4 - 6 g of 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole, and heat at 80 - 120°C to obtain sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole).
[0069] In some specific embodiments, the resin includes a resin containing a hydroxyl functional group. By selecting a resin containing a hydroxyl functional group, uniform and precise "face-to-face" coating of the sulfonated oxazole polymer is achieved, that is, the hydroxyl groups in the resin undergo in-situ polymerization with the sulfonic acid groups in the sulfonated oxazole polymer to generate sulfonate groups, uniformly coating the sulfonated oxazole polymer on the surface of the spherical resin.
[0070] In some specific embodiments, the resin includes at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, melamine-formaldehyde resin, polyester resin, vinyl resin, or polyether resin; preferably, the phenolic resin includes thermoplastic phenolic resin.
[0071] In some specific embodiments, the resin includes, but is not limited to, spherical resin.
[0072] In some specific embodiments, the preparation method of the spherical resin includes spray drying.
[0073] As an example, the preparation method of the spherical phenolic resin includes:
[0074] Phenol and formaldehyde are subjected to addition condensation reaction, and after the reaction is completed, the obtained copolymer is spray dried to obtain spherical phenolic resin.
[0075] In some specific embodiments, the solvent includes, but is not limited to, aqueous alcohol solution.
[0076] In some specific embodiments, the aqueous alcohol solution includes, but is not limited to, at least one of aqueous ethanol solution, aqueous n-propanol solution, or aqueous propylene glycol solution, preferably aqueous ethanol solution. Selecting aqueous ethanol solution as the solvent, ethanol acts as a pore-forming agent in the solvothermal process (condensation reaction), a large number of micropores are generated on the material surface, a three-dimensional hierarchical porous structure is prepared, which is beneficial to the storage of sodium ions, and after carbonization, the pore structure changes from open pores to closed pores. That is, in the present application, a sulfonated oxazole polymer is selected as the coating agent to undergo a condensation reaction with the resin in the solvent, so that the organic matter is uniformly connected to the resin surface, and after carbonization, the core is resin-based hard carbon, and the surface is the derivative carbon of the organic matter coating layer formed by chemical cross-linking of the sulfonated oxazole polymer and the resin. At the same time, selecting the solvent in the aqueous ethanol solution condensation reaction can form a large number of micropores on the material surface to form a three-dimensional hierarchical pore structure, and after subsequent calcination treatment, the microporous structure changes from open pores to closed pores, which is beneficial to the storage of sodium ions.
[0077] However, the present application is not limited to these resins and solvents, and other resins and solvents that can be used in hard carbon composites can also be used in the present application. The above-mentioned substances can be used alone or in combination of two or more.
[0078] In some specific embodiments, the volume ratio of alcohol to water in the aqueous alcohol solution is 1:(2-8). As an example, the volume ratio of alcohol to water in the aqueous alcohol solution can be any one of the point values of 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, or 1:8, or the range value between any two of them.
[0079] In some specific embodiments, the concentration of the resin in the mixed solution is 0.1-1 g / mL. As an example, the concentration of the resin in the mixed solution can be any one of the point values of 0.1 g / mL, 0.2 g / mL, 0.3 g / mL, 0.4 g / mL, 0.5 g / mL, 0.6 g / mL, 0.7 g / mL, 0.8 g / mL, 0.9 g / mL, or 1 g / mL, or the range value between any two of them.
[0080] In some specific embodiments, the mass ratio of the sulfonated dioxazole polymer to the resin is 1:(5-20). As an example, the mass ratio of the sulfonated dioxazole polymer to the resin can be any one of the point values of 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, or 1:20, or the range value between any two of them. By adjusting the mass ratio of the sulfonated dioxazole polymer to the resin within the above range, the sulfonated dioxazole polymer can be uniformly coated on the surface of the resin, achieving precise and uniform face-to-face coating; improving the reversible specific capacity, initial efficiency, cycle stability, and rate performance of the resin hard carbon material in sodium ion batteries.
[0081] In some specific embodiments, the temperature of the condensation reaction is 150-200 °C, the time of the condensation reaction is 5-15 h, and the pressure of the condensation reaction is 0-3 MPa. As an example, the temperature of the condensation reaction can be any one of the point values of 150 °C, 155 °C, 160 °C, 165 °C, 170 °C, 175 °C, 180 °C, 185 °C, 190 °C, 195 °C, or 200 °C, or the range value between any two of them; the time of the condensation reaction can be any one of the point values of 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, or 15 h, or the range value between any two of them; the pressure of the condensation reaction can be any one of the point values of 0 MPa, 0.5 MPa, 1 MPa, 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa, or the range value between any two of them. By adjusting the conditions of the condensation reaction within the above range, the sulfonic acid groups in the sulfonated dioxazole polymer and the hydroxyl groups on the surface of the resin undergo in-situ polymerization to form sulfonic acid ester groups, which is conducive to realizing the coating of the sulfonated dioxazole polymer on the resin.
[0082] In some specific embodiments, after the condensation reaction is completed, the obtained product is successively filtered, washed, and dried to obtain a hard carbon composite precursor.
[0083] In some specific embodiments, the carbonization includes staged carbonization, and the staged carbonization includes two-stage carbonization to four-stage carbonization. By adopting the process of staged carbonization, the residual carbon of the hard carbon composite precursor is significantly increased, and the structural stability of the hard carbon composite is good.
[0084] In some specific embodiments, the heating rate of the first-stage carbonization in the staged carbonization is 1-2 °C / min, the final temperature of the first-stage carbonization is 90-110 °C, and the holding time at the final temperature of the first-stage carbonization is 1-3 h. As an example, the heating rate of the first-stage carbonization in the staged carbonization can be any one point value or the range value between any two of 1 °C / min, 1.2 °C / min, 1.5 °C / min, 1.6 °C / min, 1.8 °C / min, or 2 °C / min; the final temperature of the first-stage carbonization can be any one point value or the range value between any two of 90 °C, 95 °C, 100 °C, 105 °C, or 110 °C; the holding time at the final temperature of the first-stage carbonization can be any one point value or the range value between any two of 1 h, 1.5 h, 2 h, 2.5 h, or 3 h.
[0085] In some specific embodiments, the heating rate of the second-stage carbonization in the staged carbonization is 4-6 °C / min, the final temperature of the second-stage carbonization is 200-300 °C, and the holding time at the final temperature of the second-stage carbonization is 2-3 h. As an example, the heating rate of the second-stage carbonization in the staged carbonization can be any one point value or the range value between any two of 4 °C, 4.5 °C, 5 °C, 5.5 °C, or 6 °C; the final temperature of the second-stage carbonization can be any one point value or the range value between any two of 200 °C, 210 °C, 220 °C, 230 °C, 240 °C, 250 °C, 260 °C, 270 °C, 280 °C, 290 °C, or 300 °C; the holding time at the final temperature of the second-stage carbonization can be any one point value or the range value between any two of 2 h, 2.5 h, or 3 h. During the first-stage carbonization and the second-stage carbonization, the excess alcohol solution can be removed to ensure the structural stability of the phenolic resin and reduce the volatilization caused by the thermal cracking of the material.
[0086] In some specific embodiments, the heating rate of the third-stage carbonization in the staged carbonization is 2-3 °C / min, the final temperature of the third-stage carbonization is 500-700 °C, and the holding time at the final temperature of the third-stage carbonization is 4-7 h. As an example, the heating rate of the third-stage carbonization in the staged carbonization can be any point value among 2 °C / min, 2.5 °C / min, or 3 °C / min or the range value between any two of them. The final temperature of the third-stage carbonization can be any point value among 500 °C, 520 °C, 550 °C, 580 °C, 600 °C, 620 °C, 650 °C, 680 °C, or 700 °C or the range value between any two of them. The holding time at the final temperature of the third-stage carbonization can be any point value among 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, or 7 h or the range value between any two of them. During the third-stage carbonization process, the material is pre-carbonized to regulate the growth of the carbon layer and further improve the structural stability of the hard carbon composite material.
[0087] In some specific embodiments, the heating rate of the fourth-stage carbonization in the staged carbonization is 2-3 °C / min, the final temperature of the fourth-stage carbonization is 1000-1400 °C, and the holding time at the final temperature of the fourth-stage carbonization is 2-3 h. As an example, the heating rate of the fourth-stage carbonization in the staged carbonization can be any point value among 2 °C / min, 2.5 °C / min, or 3 °C / min or the range value between any two of them. The final temperature of the fourth-stage carbonization can be any point value among 1000 °C, 1050 °C, 1100 °C, 1150 °C, 1200 °C, 1250 °C, 1300 °C, 1350 °C, or 1400 °C or the range value between any two of them. The holding time at the final temperature of the fourth-stage carbonization can be any point value among 2 h, 2.25 h, 2.5 h, 2.75 h, or 3 h or the range value between any two of them. During the fourth-stage carbonization process, heteroatoms are released, reducing the defect concentration of the hard carbon composite material and decreasing the adsorption capacity (the more the adsorption capacity, the greater the self-discharge of the material, which is not conducive to long-term storage).
[0088] Generally speaking, in this application, through the staged carbonization process, the excess alcohol solution is first removed to ensure the structural stability of the phenolic resin and reduce the volatilization caused by the thermal cracking of the material. Then, pre-carbonization treatment is carried out to regulate the growth of the carbon layer. Finally, during the carbonization process, heteroatoms are released, reducing the defect concentration of the hard carbon composite material and decreasing the adsorption capacity, improving the capacity retention rate of the material, and at the same time, the service life can also be extended. If one-step carbonization is directly carried out, the capacity retention rate of the material will be poor.
[0089] In some specific embodiments, the atmosphere for carbonization includes, but is not limited to, at least one of nitrogen, argon, or helium.
[0090] In some specific embodiments, the flow rate of the carbonization atmosphere is 50 to 100 mL / min. As an example, the flow rate of the carbonization atmosphere can be any point value among 50 mL / min, 55 mL / min, 60 mL / min, 65 mL / min, 70 mL / min, 75 mL / min, 80 mL / min, 85 mL / min, 90 mL / min, 95 mL / min or 100 mL / min, or the range value between any two of them.
[0091] In some specific embodiments, after the carbonization, it further includes: cooling the obtained product after carbonization to 20 to 30 °C. As an example, the obtained product can be cooled to any point value among 20 °C, 21 °C, 22 °C, 23 °C, 24 °C, 25 °C, 26 °C, 27 °C, 28 °C, 29 °C or 30 °C, or the range value between any two of them.
[0092] Thus, controlling the above process parameters within the given ranges is beneficial to preparing high-quality hard carbon composites, and can further improve the sodium capacity, excellent rate performance and cycle stability of the hard carbon composites of the present application. Those skilled in the art can selectively adjust one or more of the above process parameters according to the actual production situation.
[0093] As an example, the preparation of the hard carbon composite specifically includes:
[0094] Adding 5 to 50 g of a resin such as phenolic resin, epoxy resin, urea-formaldehyde resin, melamine-formaldehyde resin, polyester resin, vinyl resin or polyether resin and 1 g of a sulfonated oxadiazole polymer such as sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole) into a solvent alcohol aqueous solution such as ethanol aqueous solution, n-propanol aqueous solution or propylene glycol aqueous solution to obtain a mixed solution. The concentration of the resin in the mixed solution is 0.1 to 1 g / mL, and the volume ratio of the alcohol to water in the alcohol aqueous solution is 1:(2 to 8). A condensation reaction is carried out at 150 to 200 °C and 0 to 3 MPa for 5 to 15 h. After the condensation reaction ends, the obtained product is successively filtered, washed and dried to obtain a hard carbon composite precursor;
[0095] Carbonize the hard carbon composite precursor, and introduce an atmosphere such as nitrogen, argon or helium at a flow rate of 50-100 mL / min for segmented carbonization. Heat it to 90-110 °C at a heating rate of 1-2 °C / min and hold for 1-3 h; heat it to 200-300 °C at a heating rate of 4-6 °C / min and hold for 2-3 h; heat it to 500-700 °C at a heating rate of 2-3 °C / min and hold for 4-7 h; heat it to 1000-1400 °C at a heating rate of 2-3 °C / min and hold for 2-3 h. After carbonization, cool the obtained product to 20-30 °C to obtain the hard carbon composite material.
[0096] [Hard carbon composite material]
[0097] In some embodiments, the present invention provides a hard carbon composite material, which is prepared by the preparation method of the hard carbon composite material as described above.
[0098] It should be understood that all the features and advantages described above for the "preparation method of the hard carbon composite material" also apply to the "hard carbon composite material", and will not be repeated here one by one.
[0099] [Negative electrode sheet]
[0100] In some embodiments, the present invention provides a negative electrode sheet, which includes the hard carbon composite material prepared by the above method or the above hard carbon composite material.
[0101] Since the negative electrode sheet includes the hard carbon composite material provided in the embodiments of the present application, it can exhibit good electrochemical performance, such as high first charge and discharge capacity, excellent first Coulomb efficiency and other performances.
[0102] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is provided on the two opposite surfaces of the negative electrode current collector. It can be understood that the negative electrode active material layer can also be stacked on any one of the two surfaces of the negative electrode current collector.
[0103] The present application does not particularly limit the material of the negative electrode current collector, as long as the purpose of the present application can be achieved, and it can be selected according to actual needs. As an example, the negative electrode current collector can be made of metal materials such as aluminum, copper, nickel, stainless steel, nickel-plated steel, etc., or can be a foil material with a surface coating layer.
[0104] In some embodiments, the negative electrode active material layer includes the hard carbon composite material provided by the present application as described above. Further, the negative electrode active material layer may further optionally include a conductive agent. Further, the negative electrode active material layer may further optionally include a binder. There is no particular limitation on the types of the conductive agent and the binder in the negative electrode active material layer in the embodiments of the present application, as long as the object of the present application can be achieved.
[0105] [Battery]
[0106] In some embodiments, the present invention provides a battery, which includes the hard carbon composite material prepared by the above method, or the above-mentioned hard carbon composite material, or the above-mentioned negative electrode sheet.
[0107] In some embodiments, the above battery further includes a positive electrode sheet, an electrolyte, and a separator. That is, the battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator.
[0108] In the embodiments of the present application, in the battery, there are no limitations on the specific materials, structures, etc. of the positive electrode sheet, the separator, and the electrolyte. Components and structures known to those skilled in the art and applicable to secondary batteries can be selected, as long as the object of the present application can be achieved.
[0109] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may be a battery cell, or the battery may include a battery module (or battery pack), etc.
[0110] In some embodiments, the battery includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet. The electrode assembly may be a wound structure or a stacked structure, and the embodiments of the present application do not limit this.
[0111] In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module.
[0112] In some embodiments, the battery may be a battery pack, and the battery pack may include a box body and battery cells, and the battery cells or battery modules are accommodated in the box body.
[0113] It should be understood that multiple battery cells can be assembled into a battery module or a battery pack, and the number of battery cells included in the battery module or battery pack can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module or battery pack.
[0114] In some embodiments, the battery may be an energy storage device. The energy storage device includes an energy storage container, an energy storage cabinet, etc.
[0115] In the embodiments of the present application, the preparation methods of battery cells or batteries are well-known. In some embodiments, a battery cell can be assembled by combining a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a stacking process. The electrode assembly is placed in an outer package, dried, and then filled with the electrolyte. After vacuum packaging, standing, formation, shaping, and other processes, a battery cell is obtained. Optionally, multiple battery cells can further be combined in series, parallel, or in a hybrid connection to form a battery module. Optionally, multiple battery modules can be connected in series, parallel, or in a hybrid connection to form a battery pack. Optionally, in some embodiments, multiple battery cells can directly form a battery pack.
[0116] The present invention will be further described in detail below through examples. All raw materials used in the examples can be obtained through commercial channels.
[0117] Preparation of the coating agent
[0118] The preparation method of sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole) includes the following steps:
[0119] Mix 1 g of hydrazine sulfate, 3 g of phthalic acid, and 6 g of 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole, and heat at 100 °C to obtain sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole).
[0120] Example 1
[0121] The preparation method of the hard carbon composite material includes the following steps:
[0122] (1) Carry out an addition polycondensation reaction on toluene and formaldehyde according to a molar ratio of 7:6. After the reaction, spray dry the obtained copolymer to obtain spherical resin.
[0123] (2) Add 20 g of the spherical resin prepared above to a mixed solution of 80 mL of water and 20 mL of ethanol, then add 2 g of sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole), and carry out a condensation reaction at a pressure of 0 MPa and a temperature of 170 °C for 10 h. After the condensation reaction, filter, wash, and dry the obtained product in sequence to obtain a precursor of the hard carbon composite material.
[0124] (3) The hard carbon composite precursor is subjected to segmented carbonization treatment under a N₂ atmosphere with a flow rate of 50 mL / min. First, it is heated at a heating rate of 2 °C / min to 100 °C and held for 2 h, then heated at a heating rate of 4 °C / min to 250 °C and held for 2 h, then heated at a heating rate of 3 °C / min to 600 °C and held for 5 h, and finally heated at a heating rate of 3 °C / min to 1300 °C for high-temperature holding for 3 h. Finally, the product is cooled to 25 °C to obtain the hard carbon composite.
[0125] Example 2
[0126] A method for preparing a hard carbon composite, comprising the following steps:
[0127] (1) Toluene and formaldehyde are subjected to an addition polymerization reaction according to a molar ratio of 7:6. After the reaction ends, the obtained copolymer is spray-dried to obtain spherical resin.
[0128] (2) 20 g of the above-prepared spherical resin is added to a mixed solution of 66.6 mL of water and 33.3 mL of ethanol, and then 2 g of sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole) is added. A condensation reaction is carried out at a pressure of 0 MPa and a temperature of 170 °C for 10 h. After the condensation reaction ends, the obtained product is successively filtered, washed, and dried to obtain the hard carbon composite precursor.
[0129] (3) The hard carbon composite precursor is subjected to segmented carbonization treatment under a N₂ atmosphere with a flow rate of 50 mL / min. First, it is heated at a heating rate of 2 °C / min to 100 °C and held for 2 h, then heated at a heating rate of 4 °C / min to 250 °C and held for 2 h, then heated at a heating rate of 3 °C / min to 600 °C and held for 5 h, and finally heated at a heating rate of 3 °C / min to 1300 °C for high-temperature holding for 3 h. Finally, the product is cooled to 25 °C to obtain the hard carbon composite.
[0130] Example 3
[0131] A method for preparing a hard carbon composite, comprising the following steps:
[0132] (1) Toluene and formaldehyde are subjected to an addition polymerization reaction according to a molar ratio of 7:6. After the reaction ends, the obtained copolymer is spray-dried to obtain spherical resin.
[0133] (2) 20 g of the above-prepared spherical resin is added to a mixed solution of 80 mL of water and 20 mL of ethanol, and then 2 g of sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole) is added. A condensation reaction is carried out at a pressure of 0 MPa and a temperature of 150 °C for 10 h. After the condensation reaction ends, the obtained product is successively filtered, washed, and dried to obtain the hard carbon composite precursor.
[0134] (3) The hard carbon composite precursor is subjected to segmented carbonization treatment under an N2 atmosphere. The flow rate of the N2 atmosphere is 50 mL / min. First, it is heated to 100 °C at a heating rate of 2 °C / min and held for 2 h. Then, it is heated to 250 °C at a heating rate of 4 °C / min and held for 2 h. Then, it is heated to 600 °C at a heating rate of 3 °C / min and held for 5 h. Finally, it is heated to 1300 °C at a heating rate of 3 °C / min and held at high temperature for 3 h. Finally, the product is cooled to 25 °C to obtain the hard carbon composite.
[0135] Example 4
[0136] A method for preparing a hard carbon composite, comprising the following steps:
[0137] (1) Toluene and formaldehyde are subjected to an addition polycondensation reaction according to a molar ratio of 7:6. After the reaction, the obtained copolymer is spray-dried to obtain spherical resin.
[0138] (2) 20 g of the spherical resin prepared above is added to a mixed solution of 80 mL of water and 20 mL of ethanol, and then 2 g of sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole) is added. A condensation reaction is carried out at a pressure of 0 MPa and a temperature of 170 °C for 10 h. After the condensation reaction, the obtained product is successively filtered, washed and dried to obtain the hard carbon composite precursor.
[0139] (3) The hard carbon composite precursor is subjected to segmented carbonization treatment under an N2 atmosphere. The flow rate of the N2 atmosphere is 50 mL / min. First, it is heated to 100 °C at a heating rate of 2 °C / min and held for 2 h. Then, it is heated to 250 °C at a heating rate of 4 °C / min and held for 2 h. Then, it is heated to 600 °C at a heating rate of 3 °C / min and held for 5 h. Finally, it is heated to 1300 °C at a heating rate of 3 °C / min and held at high temperature for 3 h. Finally, the product is cooled to 25 °C to obtain the hard carbon composite.
[0140] Example 5
[0141] A method for preparing a hard carbon composite, comprising the following steps:
[0142] (1) Toluene and formaldehyde are subjected to an addition polycondensation reaction according to a molar ratio of 7:6. After the reaction, the obtained copolymer is spray-dried to obtain spherical resin.
[0143] (2) Add the 20 g of spherical resin prepared above to a mixed solution of 80 mL of water and 20 mL of ethanol, then add 2 g of sulfonated (2-(4-biphenylyl)-5-phenyl-1,3,4-oxadiazole), and carry out a condensation reaction at a pressure of 0 MPa and a temperature of 170 °C for 10 h. After the condensation reaction is completed, filter, wash, and dry the obtained product in sequence to obtain a precursor of the hard carbon composite material;
[0144] (3) Carry out a segmented carbonization treatment on the precursor of the hard carbon composite material under a N₂ atmosphere. The flow rate of the N₂ atmosphere is 50 mL / min. First, heat it at a heating rate of 2 °C / min to 100 °C and hold for 2 h, then heat it at a heating rate of 4 °C / min to 250 °C and hold for 2 h, then heat it at a heating rate of 3 °C / min to 600 °C and hold for 5 h, and finally heat it at a heating rate of 3 °C / min to 1000 °C and hold at a high temperature for 3 h. Finally, cool the product to 25 °C to obtain the hard carbon composite material.
[0145] Example 6
[0146] The preparation method of the hard carbon composite material is the same as that of Example 1, except that:
[0147] The mass of the spherical resin is 20 g, and the sulfonated (2-(4-biphenylyl)-5-phenyl-1,3,4-oxadiazole) is 1 g.
[0148] Example 7
[0149] The preparation method of the hard carbon composite material is the same as that of Example 1, except that:
[0150] The resin is epoxy resin.
[0151] Comparative Example 1
[0152] The preparation method of the hard carbon composite material includes the following steps:
[0153] (1) Carry out an addition polymerization reaction on toluene and formaldehyde according to a molar ratio of 7:6. After the reaction is completed, spray-dry the obtained copolymer to obtain spherical resin;
[0154] (2) Carry out a carbonization treatment on the precursor of the hard carbon composite material under a N₂ atmosphere. The flow rate of the N₂ atmosphere is 50 mL / min. First, heat it at a heating rate of 2 °C / min to 1200 °C and hold for 3 h. Finally, cool the product to 25 °C to obtain the hard carbon composite material.
[0155] Comparative Example 2
[0156] The preparation method of the hard carbon composite material includes the following steps:
[0157] (1) Carry out an addition polycondensation reaction of toluene and formaldehyde with a molar ratio of 7:6. After the reaction, spray dry the obtained copolymer to obtain spherical resin;
[0158] (2) Add 20 g of the spherical resin prepared above to a mixed solution of 80 mL of water and 20 mL of ethanol, keep it at a pressure of 0 MPa and a temperature of 170 °C for 10 h. After the heat preservation, filter, wash and dry the obtained product in sequence to obtain a precursor of the hard carbon composite material;
[0159] (3) Carry out a staged carbonization treatment on the precursor of the hard carbon composite material under a N2 atmosphere. The flow rate of the N2 atmosphere is 50 mL / min. First, heat it at a heating rate of 2 °C / min to 100 °C and keep it for 2 h, then heat it at a heating rate of 4 °C / min to 250 °C and keep it for 2 h, then heat it at a heating rate of 3 °C / min to 600 °C and keep it for 5 h, and finally heat it at a heating rate of 3 °C / min to 1300 °C for high-temperature heat preservation for 3 h. Finally, cool the product to 25 °C to obtain the hard carbon composite material.
[0160] Comparative Example 3
[0161] A method for preparing a hard carbon composite material, comprising the following steps:
[0162] (1) Carry out an addition polycondensation reaction of toluene and formaldehyde with a molar ratio of 7:6. After the reaction, spray dry the obtained copolymer to obtain spherical resin;
[0163] (2) Add 20 g of the spherical resin prepared above to 100 mL of water, then add 2 g of sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole), and carry out a condensation reaction at a pressure of 0 MPa and a temperature of 170 °C for 10 h. After the condensation reaction, filter, wash and dry the obtained product in sequence to obtain a precursor of the hard carbon composite material;
[0164] (3) Carry out a staged carbonization treatment on the precursor of the hard carbon composite material under a N2 atmosphere. The flow rate of the N2 atmosphere is 50 mL / min. First, heat it at a heating rate of 2 °C / min to 100 °C and keep it for 2 h, then heat it at a heating rate of 4 °C / min to 250 °C and keep it for 2 h, then heat it at a heating rate of 3 °C / min to 600 °C and keep it for 5 h, and finally heat it at a heating rate of 3 °C / min to 1300 °C for high-temperature heat preservation for 3 h. Finally, cool the product to 25 °C to obtain the hard carbon composite material.
[0165] Comparative Example 4
[0166] A method for preparing a hard carbon composite material, comprising the following steps:
[0167] (1) Toluene and formaldehyde are subjected to addition polycondensation reaction at a molar ratio of 7:6. After the reaction ends, the obtained copolymer is spray-dried to obtain spherical resin;
[0168] (2) 20 g of the spherical resin prepared above is added to 100 mL of water, and then 2 g of sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole) is added. The condensation reaction is carried out at a pressure of 0 MPa and a temperature of 170 °C for 10 h. After the condensation reaction ends, the obtained product is successively filtered, washed and dried to obtain a precursor of hard carbon composite material;
[0169] (2) The precursor of hard carbon composite material is carbonized under N2 atmosphere. The flow rate of N2 atmosphere is 50 mL / min. First, it is heated to 1300 °C at a heating rate of 2 °C / min and kept warm for 3 h. Finally, the product is cooled to 25 °C to obtain hard carbon composite material.
[0170] Application and performance testing
[0171] 1. The hard carbon composite materials in Examples 1-7 and Comparative Examples 1-4 are respectively used to prepare the negative electrode, a sodium metal sheet is used as the positive electrode, and 1.0 mol / L lithium hexafluorophosphate (LiPF6) / ethylene carbonate (EC) + dimethyl carbonate (DMC) + fluoroethylene carbonate (FEC) (the volume ratio of EC, DMC and FEC is 4.5:4.5:1) is used as the electrolyte, and a CR2032 battery is assembled in an argon glove box.
[0172] 2. The constant current charge-discharge GCD is tested by a Blue Power test system at a current density of 100 mA / g and a voltage window of 0-2 V, and the test is carried out for 100 cycles. Specifically, it includes:
[0173] (1) Test of the first discharge capacity, the first charge capacity and the Coulomb efficiency: Under the constant temperature condition of 25 °C, constant current discharge at 0.1C rate to 0 V, and record the discharge capacity at this time as the first discharge capacity; continue constant current charge at 0.1C to 2 V, and record the charge capacity at this time as the first charge capacity; the first Coulomb efficiency = first charge specific capacity / first discharge specific capacity * 100%.
[0174] (2) Test of the capacity retention rate (cycling performance): Under the constant temperature condition of 25 °C, constant current discharge at a current density of 1C to 0 V, and continue constant current charge at 1C to 2 V, which is a complete charge-discharge cycle, recorded as cycle 1. Repeat this process until the number of cycles is equal to 100, and the test ends. Record the charge capacity of the 100th cycle. Then, the capacity retention rate of the 100th cycle = charge capacity of the 100th cycle / charge capacity of the first cycle * 100%.
[0175] The test results are shown in Table 1 below.
[0176] Table 1 Performance test results of hard carbon composite materials in Examples 1-7 and Comparative Examples 1-4
[0177]
[0178]
[0179] As can be seen from Table 1, the CR2032 battery with the hard carbon composite material in Example 1 as the negative electrode has a relatively high initial storage efficiency, which is more than 90%, while the initial Coulomb efficiency of the CR2032 battery with the hard carbon composite material in Comparative Example 1 as the negative electrode is relatively low, only 68%. The higher the crosslinking degree of phenolic resin, the more the crosslinked structure can prevent the growth of carbon layers during the carbonization process. Without changing the interlayer spacing, the structure of shorter carbon layers will improve the specific capacity and cycle stability of the battery. Moreover, the higher the crosslinking degree, the more regular the shape of hard carbon, with a suitable degree of surface defects, which is helpful for improving the sodium storage performance. It can be seen from this that after sulfonating (2-(4-biphenylyl)-5-phenyl-1,3,4-oxadiazole) and coating phenolic resin, the disorder degree of resin-based hard carbon will be enhanced during the subsequent carbonization process, affecting the microstructure of the carbon layer arrangement, thereby enhancing the Coulomb efficiency of the material and improving the electrochemical performance.
[0180] In addition, through the analysis and comparison of Example 6 and Example 1, it can be seen that the mass ratio of spherical phenolic resin to sulfonated (2-(4-biphenylyl)-5-phenyl-1,3,4-oxadiazole) in Example 6 is 20:1. Compared with Example 1, the amount of sulfonated organic matter is reduced, resulting in fewer sulfonic acid groups, which may affect the coating effect on spherical resin, such as reducing the coating uniformity of spherical resin, and then affecting the cycle performance and initial efficiency of the prepared battery. Through the comparison of Example 7 and Example 1, it can be seen that different resin types will affect the performance of hard carbon composite materials. The electrochemical performance of phenolic resin-based hard carbon composite materials is better than that of epoxy resin-based hard carbon composite materials. Through the comparison of Comparative Example 4 and Example 1, it can be seen that the specific carbonization method of Comparative Example 4 is different from that of Example 1. The capacity retention rate of the battery prepared from the hard carbon composite material in Comparative Example 4 is significantly lower than that in Example 1, indicating that the direct one-step carbonization method will lead to poor capacity retention rate of the material. In the examples of the present application, through the segmented carbonization process, first remove the excess alcohol solution to ensure the structural stability of phenolic resin and reduce the volatilization caused by the thermal cracking of the material; then perform pre-carbonization treatment to regulate the growth of carbon layers. Finally, during the carbonization process, heteroatoms are released, reducing the defect concentration and adsorption capacity of the hard carbon composite material, and effectively improving the capacity retention rate of the material.
[0181] In addition, the CR2032 batteries with the hard carbon composite materials in Examples 1-7 as the negative electrodes all have good cycle retention rates (greater than 85%), showing excellent cycle stability. While the capacity retention rate of the comparative examples is only about 70-80%.
[0182] In addition, the scanning electron microscope image of the hard carbon composite material prepared in Example 1 is as shown in Figure 1 . It can be seen from Figure 1 that the spherical morphology of the hard carbon composite material is still preserved after carbonization, but there are still some cross-sections. This is because of the cross-linking effect of the organic matter, which inevitably causes adhesion between the spheres, and subsequent crushing leads to the appearance of cross-sections.
[0183] The transmission electron microscope image of the hard carbon composite material prepared in Example 1 is as shown in Figure 2 . It can be seen from Figure 2 that the structure of the coating layer and the resin-based hard carbon in the hard carbon composite material prepared in Example 1 is different, and the thickness of the coating layer is 4.624 nm.
[0184] BET test method: The nitrogen low-temperature adsorption method was used to measure the specific surface area and pore size distribution curve of the hard carbon composite materials prepared in Example 1 and Comparative Example 1;
[0185] Test process: The sample was degassed by heating and vacuum pumping to remove the impurity gases adsorbed on the surface; after weighing, the sample was placed in liquid nitrogen; at the temperature of liquid nitrogen, the nitrogen adsorption amount of the sample was measured at different pressure points to obtain the N2 adsorption / desorption curve; the data was processed by computer, and the specific surface area, pore volume, average pore size and pore size distribution were calculated from the adsorption isotherm.
[0186] The N2 adsorption / desorption curves of the hard carbon composite materials prepared in Example 1 and Comparative Example 1 are as shown in Figure 3 . Compared with the hard carbon composite material in Comparative Example 1, although the specific surface area of the hard carbon composite material in Example 1 has increased, the change is not significant. The main reason is still the change in the pore structure. After high-temperature carbonization, it is mainly a closed-pore structure. That is, pore formation improves the specific surface area, the size of the micropores, and the porosity, thereby improving the sodium storage capacity;
[0187] It was obtained by the BET test method that the specific surface area of the hard carbon composite material in Example 1 is 0.88 m 2 / g, the porosity is 0.0028 cm 3 / g, the pore size is 1.27 nm, and the specific surface area of the hard carbon composite material in Comparative Example 1 is 0.38 m 2 / g, the porosity is 0.0016 cm 3 / g, and the pore size is 1.01 nm.
[0188] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can still be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a hard carbon composite material, characterized in that: The following steps are involved: The resin, the sulfonated dioxazole polymer and the solvent are mixed to obtain a mixed solution, and a condensation reaction is performed to obtain a hard carbon composite material precursor; The hard carbon composite material precursor is carbonized to obtain a hard carbon composite material.
2. The method for preparing a hard carbon composite material according to claim 1, characterized in that: The sulfonated dioxazole polymer includes sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole); Preferably, the preparation method of the sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole) comprises the following steps: Hydrazine sulfate, phthalic acid and 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole are mixed and heated to obtain sulfonated (2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole); Preferably, the mass ratio of hydrazine sulfate, phthalic acid and 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole is 1:(2-3):(4-6); Preferably, the heating temperature ranges from 80 to 120°C.
3. The method for preparing a hard carbon composite material according to claim 1, characterized in that: The resin includes a resin containing a hydroxyl functional group; Preferably, the resin includes at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, melamine-formaldehyde resin, polyester resin, vinyl resin or polyether resin; preferably, the phenolic resin includes thermoplastic novolac resin; Preferably, the resin comprises spherical resin.
4. The method for preparing a hard carbon composite material according to claim 1, characterized in that: The solvent includes an alcohol aqueous solution; Preferably, the alcohol aqueous solution includes at least one of an ethanol aqueous solution, a n-propanol aqueous solution or a propylene glycol aqueous solution; Preferably, the volume ratio of alcohol to water in the alcohol aqueous solution is 1:(2-8).
5. The method for preparing a hard carbon composite material according to claim 1, characterized in that: The concentration of the resin in the mixed solution is 0.1 to 1 g / mL; And / or, the mass ratio of the sulfonated dioxazole polymer to the resin is 1:(5-20).
6. The method for preparing a hard carbon composite material according to claim 1, characterized in that: The temperature of the condensation reaction is 150-200°C, the time of the condensation reaction is 5-15h, and the pressure of the condensation reaction is 0-3MPa; And / or, after the condensation reaction is completed, the obtained product is filtered, washed and dried in sequence to obtain a hard carbon composite material precursor.
7. The method for preparing a hard carbon composite material according to any one of claims 1 to 6, characterized in that: The preparation method satisfies at least one of the following conditions (1) to (8): (1) The carbonization includes staged carbonization, and the staged carbonization includes two-stage carbonization to four-stage carbonization; (2) The heating rate of the first stage carbonization in the staged carbonization is 1 to 2°C / min, the final temperature of the first stage carbonization is 90 to 110°C, and the holding time of the first stage carbonization at the final temperature is 1 to 3 hours; (3) The heating rate of the second stage carbonization in the staged carbonization is 4 to 6°C / min, the final temperature of the second stage carbonization is 200 to 300°C, and the holding time of the second stage carbonization at the final temperature is 2 to 3h; (4) The heating rate of the third stage carbonization in the staged carbonization is 2 to 3°C / min, the final temperature of the third stage carbonization is 500 to 700°C, and the holding time of the third stage carbonization at the final temperature is 4 to 7h; (5) The heating rate of the fourth stage carbonization in the staged carbonization is 2 to 3°C / min, the final temperature of the fourth stage carbonization is 1000 to 1400°C, and the holding time of the fourth stage carbonization at the final temperature is 2 to 3h; (6) The carbonization atmosphere includes at least one of nitrogen, argon or helium; (7) The flow rate of the carbonization atmosphere is 50 to 100 mL / min; (8) After the carbonization is completed, the method further comprises: cooling the carbonized product to 20 to 30°C.
8. A hard carbon composite material, characterized in that The hard carbon composite material is prepared by the preparation method of the hard carbon composite material according to any one of claims 1 to 7.
9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the hard carbon composite material prepared by the method according to any one of claims 1 to 7 or the hard carbon composite material according to claim 8.
10. A battery, characterized in that: The battery comprises the hard carbon composite material obtained by the method according to any one of claims 1 to 7, or the hard carbon composite material according to claim 8, or the negative electrode sheet according to claim 9.